Continued influence of misinformation in times of COVID‐19. (26th August 2021) - van Huijstee, Dian; Vermeulen, Ivar; Kerkhof, Peter; Droog, Ellen
Abstract : Health‐related misinformation, especially in times of a global health crisis, can have severe negative consequences on public health. In the current studies, we investigated the persuasive impact of COVID‐19‐related misinformation, and whether the valence of the misinformation and recipients' degree of overconfidence affect this impact. In two pre‐registered experimental studies, participants ( N  = 403; N  = 437) were exposed to either a positive or a negative news article describing a fictional hospital's high COVID‐19 recovery/mortality rates. Half of the participants subsequently received a correction. Attitudes towards the hospital were measured before and after exposure. Results of both studies showed that, as expected, corrections reduced the persuasive impact of misinformation. But whereas some persuasive impact remained for corrected negative misinformation (a continued influence effect), it reversed for corrected positive information, causing people to have more negative attitudes towards the hospital than before exposure to any information (a backfire effect). These results corroborate prior suggestions that continued influence effects are asymmetric: negative misinformation is harder to neutralise than positive misinformation. Participants' overconfidence degrees did not have a moderating role in misinformation effects. Even though corrections decrease the persuasive impact of health‐related misinformation, continued influence remains for negative misinformation.